Enterococcus faecalis urinary-tract infections: Do they have a zoonotic origin?. Issue 4 (October 2016) - Abat, Cédric; Huart, Michael; Garcia, Vincent; Dubourg, Grégory; Raoult, Didier
Summary: Major human pathogens are frequently isolated from meat-producing animals, particularly poultry. Among them is Enterococcus faecalis, which is known to be one of the main cause of human urinary-tract infections worldwide. Early in 2015, we detected several, consecutive abnormal increases in the weekly number of human E. faecalis infections in various medical settings in the Provence-Alpes-Côte d'Azur region of France, especially including community-acquired urinary-tract infections. Speculating that this region-wide epidemiological event may have originated from animal-based food, we initiated this work to provide an overview of the epidemiology of E. faecalis, with a particular focus on the possible link between E. faecalis clones isolated from food-producing animals and those responsible for human urinary-tract infections. At that time, only one study had clearly identified strong epidemiological links between E. faecalis clones isolated from food-producing animals and human E. faecalis urinary-tract infections. This observation, coupled with our region-wide epidemiological experience, leads us to strongly believe that E. faecalis is a real zoonotic pathogen with potentially highly significant impact on human health. This is of particular concern because of its ability to acquire antibiotic-resistance genes and to infect animals and humans. Various strategies must be urgently implemented to address this public health threat, in particular through the development and implementation of large integrated automated surveillance systems based on animal and human health data to enable us to detect E. faecalis epidemiological events.